PTH-162 The Challenges of Implementing Evidence into Endoscopic Practice: A Qualitative Study. (4th June 2013) - Rajasekhar, P T; Brown, S; Nixon, C; Bramble, M; East, J; Rutter, M; Saunders, B; Rees, C
Abstract : Introduction: The Quality Improvement in Colonoscopy (QIC) study was a region wide service improvement study that aimed to improve adenoma detection rate (ADR), and thusly quality in colonoscopy, through implementation of a 'bundle' of measures to routine colonoscopy practise. These were: withdrawal time ≥ 6 minutes; routine hyoscine butylbromide use; supine position to examine the transverse colon; rectal retroflexion. Each has been shown to improve adenoma detection. The implementation of evidence into clinical practise can be challenging. We performed a qualitative interview study to evaluate factors that influenced implementation of the 'bundle' in the QIC study. Methods: The study took place in 12 units who are members of the Northern Region Endoscopy Group, a research network in the north east of England. The study team held training sessions in each unit to introduce the 'bundle', supported by a nominated local lead colonoscopist and nurse. Posters were supplied for each endoscopy room to aid promotion. Following QIC study completion units and individuals were purposively sampled for the qualitative interview study ensuring a range of units (by size, bundle uptake) were included. Semi-structured interviews were conducted until saturation was reached. Data were evaluated using thematic analysis to code and categorise interviews. Results: 119 colonoscopists participated in the QIC study. Interviews were conducted with 11 participants. 8 were lead colonoscopists, 1 a lead nurse and 3 colonoscopists who weren't leads. Increased emphasis on examination time, increased awareness of ADR as a quality marker and empowerment of endoscopy nurses to encourage use of quality measures were seen as positive impacts of introducing the 'bundle'. The simple, highly visible posters were also reported as useful in aiding study promotion. Challenges included difficulty in arranging set up meetings and in engaging certain speciality groups. Conclusion: Implementation of evidence into clinical practise can be challenging. During the QIC study, challenges included arranging staff meetings and engaging all team members. Positive outcomes included increased awareness of colonoscopy quality, particularly slower withdrawal times, and empowerment of endoscopy nurses to promote quality measures. We demonstrate that emphasis on timing of meetings and strategies to engage speciality groups should be given consideration when planning implementation of evidence or guidelines into clinical practise. Disclosure of Interest: None Declared.